pericarditis: a case report and literature review - Yuan Xie; Yanli Gu; Liang Chen (Journal of International Medical Research)
Aspergillus pericarditis is a condition characterized by nonspecific clinical features, making diagnosis challenging. Although relatively uncommon, it is associated with a low diagnostic yield and high mortality. We herein present a case of Aspergillus pericarditis alongside a review of similar cases from the literature. This report underscores the importance of enhancing clinicians’ awareness of Aspergillus pericarditis and emphasizes the need for prompt diagnosis and early initiation of treatment to improve patient outcomes.